APPROACHES AND METHODS OF ANALYSIS OF THE INFLUENCE OF INTERNATIONAL TRANSPORTATION-LOGISTICS SYSTEMS ON THE SOCIAL-ECONOMIC DEVELOPMENT OF A REGION - M. N. Styazhkin (Russian Journal of Economics and Law)
The article grounds the method of estimating the influence of transportation-logistics system on the economic development of a region, which allows to find the overall economic effect of the influence, as well as to estimate it for the existing and proposed international transportation mains. The application of the elaborated and partially probated methods and algorithms of estimation is aimed at solving the problems of optimization of international transportation-logistics systems and selecting the optimal variant of their designing, including routes tracing and main technical-economic characteristics basing on their maximal efficiency for the regional economy development.